Post-trial perceptions of a symptom-based TB screening intervention in South Africa: implementation insights and future directions for TB preventive healthcare services - Nicole Salazar-Austin; Minja Milovanovic; Nora S. West; Molefi Tladi; Grace Link Barnes; Ebrahim Variava; Neil Martinson; Richard E. Chaisson; Deanna Kerrigan (BMC, 2021)
Abstract Background Tuberculosis is a top-10 cause of under-5 mortality, despite policies promoting tuberculosis preventive therapy (TPT). We previously conducted a cluster randomized trial to evaluate the effectiveness of symptom-based versus tuberculin skin-based screening on child TPT uptake. Symptom-based screening did not improve TPT uptake and nearly two-thirds of child contacts were not identified or not linked to care. Here we qualitatively explored healthcare provider perceptions of factors that impacted TPT uptake among child contacts. Methods Sixteen in-depth interviews were conducted with key informants including healthcare providers and administrators who participated in the trial in Matlosana, South Africa. The participants' experience with symptom-based screening, study implementation strategies, and ongoing challenges with child contact identification and linkage to care were explored. Interviews were systematically coded and thematic content analysis was conducted. Results Participants' had mixed opinions about symptom-based screening and high acceptability of the study implementation strategies. A key barrier to optimizing child contact screening and evaluation was the supervision and training of community health workers. Conclusions Symptom screening is a simple and effective strategy to evaluate child contacts, but additional pediatric training is needed to provide comfort with decision making. New clinic-based child contact files were highly valued by providers who continued to use them after trial completion. Future interventions to improve child contact management will need to address how to best utilize community health workers in identifying and linking child contacts to care. Trial registration The results presented here were from research related to NCT03074799 , retrospectively registered on 9 March 2017.